Pengaruh Motivasi Belajar Siswa dan Tingkat Penghasilan Orang Tua Terhadap Minat Siswa Melanjutkan Studi ke Perguruan Tinggi - Maneza, Widhia Rahmi; Marna, Jean Elikal (Universitas Negeri Padang, 2025)
This research aims to determine how learning motivation and income from parents affect student’s desire to pursue higher education. The descriptive quantitative approach is used in this study. This study’s population consist of students from XII class SMA Negeri 3 Pariaman. The quantity of study samples was 167 people and selected by proportional random sampling. The primary data in this study was gathered by distributing questionnaires to a chosen group of students. The analytical technique applied is multiple regression analysis using SPSS 23. This results of the study shows that (1) learning motivation and income from parents affect students desire to pursue higher education (2) Learning motivation significantly predicts students' desire in pursuing higher education (3) parents income has a significant impact on students' desire in pursuing higher education